Kebijakan Perdagangan Internasional Sektor Pertanian Agreement On Agriculture (AOA) Terhadap Undang-Undang Lingkungan - Abdul Hafid Firdaus (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2022)
The decrease in green land due to conversion of agricultural land is as the increasing demand for agricultural products with the agreement in the Agreement on Agriculture, (an international trade agreement which is part of the World Trade Organization) that threatens the sustainability of environmental ecosystems. The existence of law in various aspects has a very large influence. one of the aspects is international trade activities, that the function of law is a regulator or judge in international trade activities, to provide a sense of fairness, effectiveness, and efficiency. Increasing public awareness in maintaining and preserving the environment is very important, so that ecosystem sustainability can support the development process and can achieve people's prosperity with the aim of a state. Therefore, it is necessary to have regulations or laws that regulate the environment. Currently, the issue of environmental law is one of the regulations that must be obeyed by various parties involved in international trade relations. The method in this research used the normative method, and the existing theoretical approach using books, articles, journals, or literature studies. The results of this study indicate that institutionally or existing regulations, Agreement on Agriculture (AOA) as part of the World Trade Organization (WTO) has attempted to combine international trade law with environmental law and conducted a study of international trade law regulations. The environment law establishes a commission for the protection of international trade law with environmental law and accepts the settlement of international trade and environmental cases submitted to the panel. However, because the principle of international trade is the principle of freedom, and there is no clear authority so that international trade institutions such as the World Trade Organization (WTO) have not been fully effective in regulating and defending environmental protection